2014
DOI: 10.1176/appi.ajp.2013.12121511
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Psychoanalytic Psychotherapy or Cognitive-Behavioral Therapy for Bulimia Nervosa

Abstract: Despite the marked disparity in the number of treatment sessions and the duration of treatment, CBT was more effective in relieving binging and purging than psychoanalytic psychotherapy and was generally faster in alleviating eating disorder features and general psychopathology. The findings indicate the need to develop and test a more structured and symptom-focused version of psychoanalytic psychotherapy for bulimia nervosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
160
2
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(173 citation statements)
references
References 23 publications
3
160
2
2
Order By: Relevance
“…This was true of patients with bulimia nervosa and a mixed sample of patients with bulimia nervosa or anorexia nervosa. In a recent RCT, CBT was superior to PDT [85]. This study was challenged for not having used a bona fide treatment for bulimia nervosa [86].…”
Section: Methodsmentioning
confidence: 99%
“…This was true of patients with bulimia nervosa and a mixed sample of patients with bulimia nervosa or anorexia nervosa. In a recent RCT, CBT was superior to PDT [85]. This study was challenged for not having used a bona fide treatment for bulimia nervosa [86].…”
Section: Methodsmentioning
confidence: 99%
“…These can be defined as the ''bluff syndrome'' and the ''rebound syndrome'', and are closely linked both to each other as well as with the subjective deficit of attribution/appropriation. 12 In the ''bluff syndrome'', whenever the patient is appreciated physically or for other qualities she may have, she thinks and feels that in reality she is a ''bluff'': she does not believe she really has those qualities, but believes that it is a ''trick'' and expects to be exposed at any moment to her great shame. For example, a bulimic patient tells me that a young man is attracted to her but she is sure that he must be wrong to be interested in her.…”
Section: Theoretical Observationsmentioning
confidence: 99%
“…11 Psychoanalyst with training roles in the Italian Psychoanalytic Society. 12 With this term, R. Cahn describes the process of ''becoming-asubject'' and the difficulty of ascribing mental experiences appertaining to the subject to the Self. could say that this positive appraisal ''rebounds'' off her without affecting her feelings of the self and without touching or increasing her positive feelings; when Ilenia's boss awards her a pay rise that she has not put in for, for excellent productivity, she is not able to credit herself with possessing such high professional qualities and therefore increase her self-esteem.…”
Section: Theoretical Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Females consume lots of food and drinks; depression follows, anxiety, and hypochondriacally neurosis because their obesity leads to body image distortion. (Koff, Stabbs, & Redam, 1990;Poulsen et al, 2014) Many theories explained anorexia nervosa, The biological theory advocates found that the first kens of anorexia nervosa patients (degree 1) are more likely to be have bulimia nervosa, Anorexia nervosa patients affect closed relatives up to eight times compared with individuals other than relatives (Shqair, 1999). The prevalence of the disorder of an infected family member with his brothers and sisters or twins percentage scored (6-10%) compared to (1-2%) with nonrelatives (Dosoqi, 2006;Othman, 2001).…”
Section: Introductionmentioning
confidence: 99%